ANALYSIS OF POCKET MONEY MANAGEMENT BASED ON FINANCIAL LITERACY LEVELS IN INDONESIAN MASTER VOCATIONAL SCHOOL STUDENTS - I Nyoman Suri Adnyana; Rahmatullah Rahmatullah; Didi Sukardi; Murdiyono Murdiyono (Yayasan Nusantara Hasana Berdikari, 2022)
This study aims to analyze pocket money management based on the level of financial literacy among students at the Indonesian Master Vocational School (SMK Master Indonesia). Financial literacy is a crucial factor in shaping adolescents' financial behavior, particularly in their daily use of pocket money. The research method used a quantitative approach, distributing questionnaires to students at the Indonesian Master Vocational School as respondents. The results show that students with a high level of financial literacy tend to have better abilities in managing expenses, saving, and distinguishing between needs and wants.